Do We Have Adequate Flexion-extension Radiographs for Evaluating Instability in Patients With Lumbar Spondylolisthesis?. Issue 1 (1st January 2020) - Morita, Tomonori; Yoshimoto, Mitsunori; Terashima, Yoshinori; Tanimoto, Katsumasa; Iesato, Noriyuki; Ogon, Izaya; Oshigiri, Tsutomu; Teramoto, Atsushi; Emori, Makoto; Takashima, Hiroyuki; Hirota, Ryosuke; Fujimoto, Shutaro; et al.
Abstract : Study Design: A retrospective cohort study of consecutive patients. Objective: To investigate whether adequate flexion-extension was acquired in standard functional radiographs in lumbar spondylolisthesis. Summary of Background Data: In lumbar spondylolisthesis, flexion-extension radiographs taken in the standing position are most commonly used to evaluate spinal instability. However, these functional radiographs occasionally depend on the patient's effort and cooperation, they can provide different results. Methods: This study included 92 consecutive patients diagnosed with L4 -5 degenerative lumbar spondylolisthesis. We analyzed the flexion-extension radiographs taken with the patient being led by the hand (LH) and those taken without LH (NLH). Sagittal translation (ST), segmental angulation (SA), posterior opening (PO), and lumbar lordosis (LL) were measured on functional radiographs taken in both tests. Then, ST, SA, PO, detection rate of instability, and LL observed in LH were compared with those observed in NLH. Furthermore, the correlation of the difference was evaluated between ST, lumbar angulation, and LL. Results: A relative value of ST was 9.5% ± 4.3% in LH and 5.6% ± 3.3% in NLH, which differed significantly ( P < 0.001). SA and PO were also significantly greater in LH than in NLH. The detection rate of instability was 71.7% in LH and 30.4% in NLH ( P < 0.001). LL measurement on flexion showed 17.6° ± 13.5° in LH and 28.2° ± 12.2° in NLH, which differed significantly ( P < 0.001). However, no significant difference was found in LL on extension between LH and NLH. There was a moderate correlation between the difference of ST, SA, PO, and LL on flexion. Conclusion: Flexion with physical assistance was useful for the detection of abnormal lumbar mobility. Taking radiation exposure into consideration, physical assistance such as using a table in front of a patient could lead the similar evaluation of the segmental instability. Level of Evidence: 2 Abstract : In lumbar spondylolisthesis, flexion-extension radiographs taken in the standing position occasionally depend on the patient's effort and cooperation. So they can provide an underestimation of lumbar instability. To detect a reliable instability, not extension but flexion may be important and be acquired significantly greater with light physical assistance.